Skin masses in dogs under one year of age. (31st August 2021) - Kim, D.; Dobromylskyj, M. J.; O'Neill, D.; Smith, K. C.
Abstract : Objectives: To utilise a large histopathology database to ascertain the incidence and nature of skin masses in young dogs from 0 to 12 months of age. Materials and Methods: A total of 2554 submissions received for histopathology from dogs 0 to 12 months of age, clinically diagnosed with a skin mass between 2006 and 2013, were retrieved from the database of a large commercial diagnostic laboratory. The histological diagnosis and site of the lesion, together with age, breed and sex of the dog were recorded. Results: The most common skin mass found in this study was histiocytoma (n=2212, 86.6%). The majority of all submissions were neoplastic (n=2408, 94.3%), and most of those were benign (n=2372, 98.5%). Almost all of the benign neoplastic lesions were of round cell origin (n=2229, 94.0%) whereas most of the non‐neoplastic lesions were derived from the epithelium (n=136, 93.8%). The five most commonly diagnosed skin masses in young dogs were histiocytoma, papilloma, dermoid cyst, follicular cyst and mast cell tumour. A male predisposition was shown for histiocytoma (odds ratio 1.72) and mast cell tumour (odds ratio 2.18) with a strong site predilection for the limb region (30.8% and 27.8% respectively). Dermoid cysts and follicular cysts were most commonly found in the skin of the abdomen (64.7% and 52.3% respectively) with boxers being predisposed (25.9% of dermoid cyst and 25.0% of follicular cyst). Clinical Significance: A large proportion of skin mass submissions in young dogs were neoplastic and benign. Also, the most common skin mass in young dogs was found to be histiocytoma. Tumours can occur in this age group and should be considered as a potential differential diagnosis also in young patients presenting with a skin mass.